Museum alive with David Attenborough [videorecording (DVD)] - Attenborough, David, 1926- (PBS Distribution, 2025)
Sir David Attenborough explores the Natural History Museum in London and meets some of the most extraordinary creatures from the past. These animals are brought back to life using state of the art CGI informed by the latest scientific understanding, which allows him to come face to face with a saber-toothed tiger, dodge a giant eagle, and evade a colossal snake.